INFLUENCE BIOAGROTECHNOLOGY CULTIVATION OF WINTER TRITICALE WHEN CONSIDERING THE ELEMENTS OF THE STRUCTURE OF GRAIN YIELD - Писаренко, П. В.; Москалець, В. В.; Москалець, Т. З.; Москалець, В. І. (Scientific Progress & Innovations, 2013)
Conducted a study on the sensitivity of winter triticale on the action of microbiological preparations albobakterin and diazobakterin when considering the elements of the structure of grain yield. It is established that the use of microbial preparations in on winter triticale allowed to differentiate varietal composition of the this culture in terms of sensitivity to the action of microorganisms: sensitive (on diazobakterin: «Аmphidiploids 256», «Slavetne»; on albobakterin: «Vivate Nosivsky», «Jaguar», «Augusto», «Slavetne»), moderately sensitive (on diazobakterin: «Augusto») and insensitive (on diazobakterin: «Vivate Nosivsky», «Jaguar», «DAU 5»; on albobakterin: «Аmphidiploids 256», «DAU 5»), depending on the actions of certain biological preparations for a specific grade. Proved that triticale varieties «AD 256», «Slavetne» and «Vіvate Nosіvsky» under the influence of microbial agents to provide high grain yield 7–8t/ha by increasing the number of flowers from the main ears of corn, of grains from the main ear of corn and weight of grains from the main spike and plant weight of 1000 gm.